PTU-110 What impact do hcv infection and subclinical cryoglobulinaemia have on the b cell repertoire?. (22nd June 2015) - Swann, R; Bashford-Rogers, R; Robinson, M; Mills, PR; Barclay, S; McLauchlan, J; Kellam, P; Patel, A
Abstract : Introduction: In addition to causing liver injury, hepatitis C virus (HCV) is closely associated with clonal B-cell pathologies such as cryogloglobulinaemia. 1 The virus is also capable of evading control by antibody responses. 2 Understanding the mechanisms by which HCV resists clearance by the adaptive immune system is important in vaccine design. We hypothesised that HCV infection may restrict the B-cell repertoire, predisposing to clonal B-cell disorders and contributing to impaired ability to mount an effective anti-viral antibody response. We aimed to explore this by determining: Any differences in B-cell Receptor (BCR) characteristics between HCV-infected individuals with and without cryoglobulinaemia. Any functional differences in viral neutralising ability associated with subclinical cryoglobulinaemia. Method: Patients chronically infected with either genotype 1 (G1) or genotype 3 (G3) HCV were prospectively recruited in addition to healthy controls (HC). None had a prior diagnosis of cryoglobulinaemia. Patient serum was tested for presence of cryoprecipitates. Purified IgG from patient serum was tested for ability to prevent infection of cultured cells by a panel of HCV envelope-coated 'pseudoparticles'. For a subset of HCV-infected patients and HC, RNA was extracted from PBMCs and cDNA libraries generated. BCR genes were amplified and underwent 454 sequencing. Sequences were analysed for overall diversity, clonality and specific gene usage using an in-house programme. Results: 75 HCV-infected patients (36 G1, 39 G3) were recruited. Of the HCV-infected individuals, 28% (21/75) had detectable cryoprecipitates. There was no association between presence of cryoglobulins and functional antibody responses (p = 0.77). BCR sequences were analysed for 6 cryoglobulin positive, 6 cryoglobulin negative and 6 HC. There was no difference in overall BCR diversity between the groups. Cryoglobulin positive individuals showed reduced expression of IGHV 1–8 (p = 0.004). The antigen binding CDR3 region was longer in cryoglobulinaemic individuals than HC (p = 0.028). Conclusion: Our data suggest that asymptomatic cyoglobulinaemic antibodies are common in chronic HCV infection. While these are not associated with an obvious deficit in antibody function or BCR diversity, next generation sequencing has revealed potentially important differences in their B-cell receptor populations. These novel findings and their functional implications require further analysis. Disclosure of interest: None Declared. References: Charles ED, et al . Blood 2008;111:1344–1356 Edwards VC, et al . J Gen Virol. 2012;93:1–19